Production of γγ＋2 jets from double parton scattering in proton-proton collisions at the LHC - 陶军全 张思靓 沈玉乔 范嘉伟 陈国明 陈和生 (Chinese physics C, 2015)
Cross sections for the production of pairs of photons plus two additional jets produced from double parton scattering in high-energy proton-proton collisions at the LHC are calculated for the first time. The estimates are based on the theoretical perturbative QCD predictions for the productions of γγ at next-to-next-to-leading-order, jet＋jet and γ＋jet at next-to-leading-order, for their corresponding single-scattering cross sections. The cross sections and expected event rates for γγ＋2 jets from double parton scattering, after typical acceptance and selections, are given for proton-proton collisions with the collision energy s=13 TeV and integrated luminosity of 100 fb-1 planned for the following years, and also s=14 TeV with 3000 fb 1 of integrated luminosity as the LHC design.